Microencapsulation of the Biocide Benzisothiazolinone (BIT) by Inclusion in Methyl-β-cyclodextrin and Screening of Its Antibacterial and Ecotoxicity Properties - Vânia F. M. Silva; Aurora Silva; Ermelinda M. P. J. Garrido; Fernanda Borges; Alexandra Gaspar; Jorge M. P. J. Garrido (Toxics)
The excessive use of biocides has considerable environmental and economic impacts; this is why new technologies have been sought to decrease the concentration levels applied in an effort to reduce the use of these substances. Microencapsulation using cyclodextrins has been widely used in the food and pharmaceutical industries as a way of reducing the concentrations of the active substance necessary to achieve a biological effect and/or eliminate its irritating or toxicological effects. In this study, the inclusion complexation behavior and binding ability of benzothiazolinone (BIT) with different β-cyclodextrins (β-CD, HP-β-CD, and Me-β-CD) was investigated. The intermolecular interactions were examined through UV and FTIR spectroscopy, DSC, 1D 1H NMR, and 2D ROESY. The highest stability constant was observed for the BIT/Me-β-CD inclusion complex (299.5 ± 2.9 M−1). Antibacterial activity was investigated against Staphylococcus aureus and Escherichia coli, and the results revealed that the BIT/Me-β-CD inclusion complex displays a higher antibacterial activity than BIT. The acute toxicity of the biocide and inclusion complex was also examined using the photobacterium Aliivibrio fischeri. Although BIT exhibited higher toxicity than the inclusion complex, further investigation is needed due to the quorum quenching effect of β-CDs. The data found suggest that BIT microencapsulation can increase its aqueous solubility and can be used as an effective tool to improve its chemical, biological, and ecotoxicological properties.